THE EFFECT MIND MAPPING MODEL IN SCIENCE LEARNING - Made Susilawati; Yuyun Suprapto; Loso Judijanto; Imam Subasman; Tomi Apra Santosa (International Journal of Teaching and Learning, 2023)
The purpose of the study was to determine the influence of the mind mapping model on science learning. This type of research is a meta-analysis study. The data source came from an analysis of 11 national and international journals. Research inclusion criteria are research must be indexed Science and Technology Index (SINTA), DOAJ, Scopus and Web of Science (WOS), Research published in 2017-2023, research must be experimental methods, Research has a relationship between mind mapping models in science learning, Research must be in the form of international journals or proceedings, Journals must use Indonesian and English, and publications obtained by the Google Scholar database base, Frontiers journal, ERIC, ProQuest and Wiley. Data analysis by calculating the effeck size of the entire study, heterogeneity test, analyzing publication bias and p-value test to test the hypothesis with JSAP application. The results concluded that the average value of summary effect size was 0.67 medium criteria. This finding explains that the mind mapping model has a relatively moderate positive effect on science learning. The moderator's analysis showed more effective mind mapping models at the educational level and sample size.